Estimation of Far-field Coseismic Deformation Caused by the Recent Giant Earthquakes - Nguyen, Anh Duong (H. : ĐHQGHN, 2017)
In this paper, we estimate coseismic displacements in Vietnam caused by the 2004 Sumatra and the 2011 Tohoku earthquakes using static fault models in a layered spherical earth model. We find that the 2004 Sumatra earthquake caused southwestward movement of about 56 mm in Southern Vietnam and gradually decreasing to the north. While the 2011 Tohoku earthquake moved the area in the opposite direction, by about 0.9 mm to the east and about 0.4 mm to the north. The difference in amplitude of coseismic displacements is due to the distance from each source fault to the study area and the compact slip region of the 2011 Tohoku earthquake affected to the size of coseismic deformation area. Our results indicate that it is necessary to take into consideration of the coseismic deformation induced by the giant earthquakes on discussion of tectonic deformation in Vietnam.